Bullying Experiences Among First Nations Youth: Identifying Effects on Mental Health and Potential Protective Factors - Dunlop, Caely I (2016)
Bullying represents a substantial issue facing Canadian youth, and is associated with negative outcomes across domains of function throughout the lifespan. Despite significant literature examining bullying involvement among adolescents in Canada, a paucity of research explores the bullying experiences of First Nations, Metis and Inuit (FNMI) youth. This is particularly concerning, as these youth may be at higher risk for bullying and its related consequences due to the cultural marginalization and systemic inequalities experienced by Indigenous peoples nationwide. The present study aims to address this gap in the literature, examining the bullying experiences of FNMI youth, the effects of these experiences on mental health and well-being, and the potential moderating effect of three protective factors (cultural, school and peer connectedness), using longitudinal data collected from a cohort of FNMI adolescents in a large school district in southwestern Ontario. Findings indicated that FNMI youth in this sample experienced increased bullying victimization and perpetration as compared to national averages, and that greater cumulative bullying victimization was associated with more negative mental health. Further, despite no apparent moderating effect, all three of the identified protective factors predicted mental wellbeing independent of bullying victimization. Results support a tiered approach to intervention, confirming the merit of culturally relevant, school-based programming that incorporates these factors, as well as suggesting the need for targeted bullying interventions to promote resilience and well-being, and mitigate risk among FNMI youth experiencing bullying